dan, di PERANCANGAN TEMPAT PENGOLAHAN SAMPAH REDUCE-REUSE-RECYCLE (TPS 3R) DI KELURAHAN KUIN CERUCUK KOTA BANJARMASIN - Prabowo, Ien Yus Rizal; Firmansyah, Muhammad; Abdi, Chairul; Khair, Riza Miftahul (Jernih: Jurnal Tugas Akhir Mahasiswa, 2025)
Waste is a problem that is often experienced in urban areas, including the City of Banjarmasin. In big cities, waste is a problem both in terms of quantity and type. The size of the waste problem grows along with the growth of the population in the city. The increase in population causes an increase in population activity which also means an increase in the amount of waste generation. Hoarding is one of the most common ways of disposing of municipal solid waste. As happened in Kuin Cerucuk Village, Banjarmasin City which has a population of 19 467 people with a population density of 11,727.11 people/km2. As an effort to overcome the problem of waste generation in Kuin Cerucuk Village is to plan a TPS 3R. In making a waste building design, it is necessary to have both population projections and waste generation projections. From the results of the design of the buildings contained in the TPS 3R in the form of a receiving area, inorganic room (sorting area, plastic waste reception area, processed plastic waste reception area, milling area and washing area), inorganic room (organic reception area, enumeration area, composting area and sieving area), warehouse buildings, and supporting facilities (offices, toilets, prayer rooms and ablution areas). The land requirement for this design is an area of ​​1,110 m2 with a Budget Plan of Rp. 3,017,465,295.09.